2017
DOI: 10.3847/1538-4357/837/1/15
|View full text |Cite
|
Sign up to set email alerts
|

On the Incidence of Wise Infrared Excess Among Solar Analog, Twin, and Sibling Stars

Abstract: This study presents a search for IR excess in the 3.4, 4.6, 12 and 22 µm bands in a sample of 216 targets, composed of solar sibling, twin and analog stars observed by the WISE mission. In general, an infrared excess suggests the existence of warm dust around a star. We detected 12 µm and/or 22 µm excesses at the 3σ level of confidence in five solar analog stars, corresponding to a frequency of 4.1 % of the entire sample of solar analogs analyzed, and in one out of 29 solar sibling candidates, confirming previ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 72 publications
1
3
0
Order By: Relevance
“…These bodies can give fundamental informations about the chemistry and evolution of protoplanetary disk and the planetary systems they form. Despite a similar physical mechanism to be expected in the production of the reported debris disks, our findings show that stars with physical parameters similar to the Sun, as is the case of the whole sample here analyzed, can in fact be very different from the Sun once the star and its circumstellar environment are considered, confirming previous results by Da Costa et al (2017). Among these physical parameters, age is an important one for determining the presence of debris disks.…”
Section: Searching For Ir Excesssupporting
confidence: 86%
See 2 more Smart Citations
“…These bodies can give fundamental informations about the chemistry and evolution of protoplanetary disk and the planetary systems they form. Despite a similar physical mechanism to be expected in the production of the reported debris disks, our findings show that stars with physical parameters similar to the Sun, as is the case of the whole sample here analyzed, can in fact be very different from the Sun once the star and its circumstellar environment are considered, confirming previous results by Da Costa et al (2017). Among these physical parameters, age is an important one for determining the presence of debris disks.…”
Section: Searching For Ir Excesssupporting
confidence: 86%
“…Although the presence of debris disks, with asteroid belt characteristics, is now well established for hundreds of stars (Chen et al 2006;Cotten & Song 2016;Trilling et al 2008;Weissman 1995;Aumann et al 1984;Patel et al 2014), the present day literature pints for a scarcity of asteroid belt signatures around Sun-like stars (Da Costa et al 2017;Sibthorpe et al 2018). For instance, a recent study has shown a null detection of warm debris around solar twin stars (Da Costa et al 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An important point is that eq. ( 6) describes the behaviour of the disc-less stars and, therefore, it is not suitable for very young stars, because they have a thick dust disc in the infrared [40]. On the other hand, accreting stars have a physics more complex than that of non-accreting stars, because the star-disc interaction controls the rotation [41].…”
mentioning
confidence: 99%